Evaluation of the effect of chin prosthesis implantation on mentalis muscles based on three-dimensional imaging technology - Cao, Jie; Zhuang, Jun; Wang, Cheng; Kong, Xiangting; Chen, Yi; Su, Xueshang; Wei, Qingqian; Zhang, Ziming; Guo, Fengfeng; Hu, Jintian (Journal of plastic, reconstructive & aesthetic surgery, 2024)
Chin prosthesis implantation, a cosmetic procedure to correct chin asymmetry, depression, or retraction, is generally safe and simple. However, its long-term effects on surrounding tissues are a concern. This study aimed to use three-dimensional (3D) scanning to classify the mentalis muscle shapes and assess the impact of prosthesis implantation on these muscles. This study evaluated 450 eligible female participants. Using three-dimensional imaging, data on the types, thickness, width, and length of the left and right mentalis muscles were collected and summarized. The impact of chin prosthesis on these muscle dimensions was assessed using analysis of variance, and the effect on muscle type was determined using χ2 test. Chin implant placement affected the mentalis muscles, resulting in increased length, thickness, and width. The subjects’ mentalis muscles were categorized into 3 types and divided into 7 subtypes. χ2 test results indicated that implantation influences the classification of these muscles. Recognizing how implant placement affects the mentalis muscle can guide the development of treatments to mitigate these changes. Additionally, understanding the muscle’s morphology enables more precise treatment approaches for patients.